Changes in Nutritional and Sensory Qualities of Cookies Supplemented with Macadamia Oil Cake - Hoang Van Chuyen,; Thanh Ngan Nguyen , (Journal of Technical Education Science, 2024)
The objective of this study was to investigate effect of the addition with different ratios Macadamia oil cake (MOC) on physical properties (color and texture), nutritional composition (moisture content, protein content, fat content, fiber and energy value) and sensory quality of cookies were investigated. The addition of MOC results in the increases of protein, ash and fat content, while carbohydrate content, by contrast, decreased in the cookies. Regarding the physical properties, the thickness and breaking strength of cookies showed significant differences between the fortified samples and the control while diameter, and spread ratio did not reveal any variations. For the sensory quality, score of color, flavor, texture, taste, except overall acceptability of fortified cookies witnessed a significant difference (p<0,05). The microbiological analyses also confirmed that the fortified cookies satisfy the microbial safety standards. Based on the observed results, the addition with 15% of MOC is recommended for developing cookie products to improve nutritional and sensory qualities The nutritional analysis of the cookies supplemented with 15% macadamia oil cake confirmed that product contains 9.96g protein, 26.50g fat, 55.80g carbohydrate, 3.08g dietary fiber and an estimated energy of 501.58 kcal in each 100 grams.